Incidence of Pododermatitis in Broiler Reared under Two Types of Environment - Jacob,FG (2016)
ABSTRACT Housing environment is essential to achieve good broiler performance and to prevent diseases, including footpad dermatitis (FPD). The objective of this study was to determine the incidence of footpad dermatitis in broilers chickens according to housing type. The study was carried out with broilers reared for 5, 12, 19, 29 and 40 days. Four houses were used in this observational study. House 1 (A1) had positive pressure and reused litter; house 2 (A2) had positive pressure and new litter (sawdust); house 3 (A3) had positive pressure and new litter (rice husks); and house 4 (A4) had negative pressure and reused litter. During the entire experiment, air environmental and litter surface temperatures, and litter compaction were recorded. Pododermatitis was assessed by visual scoring of the footpads. Footpads were scored as function of the severity of the lesion. The comparison of means by the test of Bonferroni at 95% confidence interval showed higher incidence of footpad dermatitis in A3, probably due to the particle size of litter substrate. The lowest footpad dermatitis incidence was found in A1, with reused sawdust litter.